2013
DOI: 10.1001/jamaneurol.2013.172
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Disease

Abstract: Importance Mutations in the gene encoding parkin (PARK2) are the most common cause of autosomal recessive juvenile-onset and young-onset parkinsonism. The few available detailed neuropathologic reports suggest that homozygous and compound heterozygous parkin mutations are characterized by severe substantia nigra pars compacta neuronal loss. Objective To investigate whether parkin -linked parkinsonism is a different clinicopathologic entity to Parkinson disease (PD). Design, Setting, and Participants We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 41 publications
1
71
1
Order By: Relevance
“…[10-20] Common pathologic features have included severe neuronal loss in the substantia nigra (SN), variable neuronal loss in the locus coeruleus (LC), and relatively rare Lewy body pathology. [20]…”
Section: Introductionmentioning
confidence: 99%
“…[10-20] Common pathologic features have included severe neuronal loss in the substantia nigra (SN), variable neuronal loss in the locus coeruleus (LC), and relatively rare Lewy body pathology. [20]…”
Section: Introductionmentioning
confidence: 99%
“…Parkin related PD had clinical and pathologic features that might show varying degrees of difference with idiopathic PD (Doherty et al., 2013). Young onset age, more symmetric involvement, dystonia at presentation, brisk deep tendon reflexes, a good response to levodopa therapy (Lohmann et al., 2003; Lucking et al., 2000), and more symmetric and more marked reduction of dopamine uptake on 123I FP‐CIT SPECT scan (DaTSCAN) were found in Parkin ‐related disease (McNeill et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In PD, degeneration of the olfactory nucleus with impairment of smell starts early in Braak stageI(Braak et al., 2003) and was thought to be specific for Lewy body‐type neurodegeneration. The PD ‐Parkin patients had less extensive distribution of Lewy bodies neuropathology, that might not follow Braak staging and spares olfactory structures (Doherty et al., 2013; Gouider‐Khouja et al., 2003), and might explain their preserved olfaction. The absence of Lewy bodies in patients with Parkin mutations suggested that Parkin might be required for the formation of Lewy bodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations